THEORETICAL ASPECTS OF TRANSFORMATIONAL LEADERSHIP - Vonoga, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Leadership is one of the important topics in today's economic science. The topicality of the research is based on economic development requirements. Leadership influences important processes and development in the company. The paper contains a theoretical analysis of the term , transformational leadership” aspects presented in scientific literature and a determination of transformational leadership structure and research results. In the paper, the author researches four dimensions of transformational leadership. The research is based on an analysis of the specific literature and scientific publications, research papers, studies, survey results and other sources of information. Research methods: the monographic or descriptive method for research of the transformational leadership concept, the interview method. The aim of the paper is to research the conception and theoretical aspects of transformational leadership in contemporary economic science in order to develop suggestions for a company’s leaders. Tasks of the paper: to find out the main aspects of the term , transformational leadership”; to make interviews with a company’s leaders in order to clarify transformational leadership influence on interactions between the leaders and their followers; to develop conclusions and suggestions. The author concludes that main aspect of transformational leadership is symbiosis between the leader and the followers - transformational leaders transform the personal values of their followers to support the vision and goals of the organization.